Mapping the Paradigm Shift in Teachers’ Roles: A Bibliometric and Survey-Based Analysis in 21st-Century Education - Sigit Wibowo; Siti Fatimah; Nuril Nuzulia; Suyono Suyono; Oktaviani Adhi Suciptaningsih; Zahid Zufar At Thaariq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Rapid social and digital transformations have fundamentally reshaped education systems, leading to a redefinition of teachers’ roles in the 21st century that extends beyond technological integration to encompass epistemological, pedagogical, and structural changes. This study aims to analyze the conceptual structure, intellectual evolution, and global collaboration patterns of the paradigm shift in teachers’ roles, while also examining its empirical manifestation in practice. A mixed-method approach with an integrative design was employed, combining a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, bibliometric analysis, and a quantitative survey. Data were retrieved from the Scopus database (2016–2026), resulting in 85 peer-reviewed articles following a rigorous selection process, and complemented by survey responses from 80 teachers across Indonesia. Bibliometric mapping using VOSviewer reveals that the emerging paradigm is structured across three interrelated dimensions: pedagogical, technological, and structural. The pedagogical dimension reflects a shift from knowledge transmission to collaborative knowledge co-construction, while the technological dimension indicates a transition from ICT integration toward the adoption of artificial intelligence and data-driven adaptive learning systems. The structural dimension highlights the strengthening of teacher agency, reflective professionalism, and the restructuring of teacher education systems. Network analysis shows that global research collaboration remains regionally fragmented, whereas co-citation patterns indicate the emergence of core references, suggesting an ongoing phase of conceptual consolidation. Empirical findings confirm strong pedagogical and professional transformation in practice but reveal a gap in the adoption of advanced technologies such as AI. This study contributes by proposing a multidimensional typology of teachers’ roles—as facilitators, digital learning designers, institutional change agents, and ethical technology curators—thereby advancing theoretical consolidation and providing a foundation for systemic policy reform in 21st-century education.